A Socio-Historical Consideration of Collegiate Physical Education in Modern Korean History. Issue 12 (13th August 2017) - Kim, Hyun-Duck
Abstract: South Korea has demonstrated incredible growth and become a high-tech industrialized economy over the last five decades. During this era of rapid economic advancement, sports has been an important subject associated with the country's political, social, cultural, and educational concerns. Especially, higher education has undergone extensive transformation and expansion with the influence of globalization. The influx of advanced technology and information, society's modern needs, and lifestyle changes has affected many academic programs, including physical education. Although physical education and sport studies are promising academic fields because of emerging career opportunities, disparities between the academic training provided by tertiary institutions and the skills needed in sports-related industries are evident. This paper examines socio-historical events related to Korean physical education and sports, recent curricula and structural challenges, and the proposed convergence of sport disciplines and the development of professional competencies for improving the quality of physical education and sports in the country.